(untitled) (Indian Journal of Public Health Research & Development, 2021)
Diabetes mellitus is a metabolic disease characterized by glucose levels in the blood that are more than normal or hyperglycemia, this is due to a decrease in the body’s ability to react with insulin, or it could be impaired insulin secretion.Riskesdas 2013 shows that diabetes mellitus sufferers in Indonesia are around 6.9% or around 12 million people with 1.4% of diabetes sufferers in South Kalimantan or around 38,113 people diagnosed with diabetes mellitus, especially type 2 diabetes mellitus which is related to lifestyle.One of the efforts made is health education. This research is an experimental research using pre-experimental method with one group pretest-postest design. The sampling technique used consecutive sampling of 50 people.The results of the effect of health education on the behavior of diabetes mellitus sufferers obtained p-value = 0.011<0.05, this indicates that Ho is rejected, which means that there is an effect of health education on the behavior of diabetes mellitus sufferers in handling diabetes mellitus.The results of the effect of health education on the knowledge level of diabetes mellitus sufferers obtained p-value = 0.421> 0.05, this indicates that Ho is accepted, which means that there is no effect of health education on increasing knowledge of diabetes mellitus sufferers in handling diabetes mellitus. These results were obtained from the pre and post-test scores of the respondents which indicated that there was an influence before and after health education to the public.